Exercise capacity improvement after cardiac rehabilitation following myocardial infarction and its association with long-term cardiovascular events. (17th April 2021) - Novaković, Marko; Novak, Tjaša; Vižintin Cuderman, Tjaša; Krevel, Barbara; Tasič, Jerneja; Rajkovič, Uroš; Fras, Zlatko; Jug, Borut
Abstract: Aims : Cardiovascular rehabilitation (CR) improves aerobic capacity and quality of life in patients after myocardial infarction (MI). The aim was to examine the associations between exercise capacity improvement and different clinically relevant cardiovascular events. Methods and results : This was a registry-based study of post-MI patients, referred to CR. All patients were submitted to exercise testing before and after CR (36 sessions, 2–3 times/week, and combined exercise). Patients were divided into two groups, based on the difference in exercise capacity before and after the CR programme with the cut-off of two metabolic equivalents (METs) improvement. We assessed the correlation between the extent of exercise capacity improvement and the following cardiovascular events: major adverse cardiac events (MACE), cardiovascular-related hospitalizations, and unplanned coronary angiography. A total of 499 patients were included (mean age 56 ± 10 years, 20% women). Both groups significantly improved in terms of exercise capacity, natriuretic peptide levels, resting heart rate, and resting diastolic pressure; however, lipid status significantly improved only in patients with ≥2 METs difference in exercise capacity. A total of 13.4% patients suffered MACE (median follow-up 858 days); 21.8% were hospitalized for cardiovascular reasons (median follow-up 791 days); and 19.8% had at least one unplanned coronary angiography (median follow-up 791 days). Exercise capacity improvement of ≥2 METs was associated with lower rates of MACE, cardiovascular hospitalizations, and unplanned coronary angiography in all examined univariate and multivariate models. Conclusion : This study has shown that exercise improvement of ≥2 METs is associated with a significant decrease in MACE, cardiac hospitalizations, and unplanned coronary angiography.